Desain Komik Digital untuk Kepantasan Berbahasa Sunda pada Remaja Kota Bandung - Sulistio, Fajar; Ekawardhani, Yully Ambarsih (Fakultas Desain Universitas Komputer Indonesia, 2022)
This article highlights the visualization of characterizations that display the attributes of Sundanese culture, and communication using the Sundanese language. One of the regional languages ​​in Indonesia is Sundanese, which is found in the Sundanese tribe. Until now it is still one of the languages ​​that are often used in the life of the Sundanese people, such as the city of Bandung. aims to find out how the people of Bandung, especially teenagers, can understand the appropriateness of Sundanese language. This is shown in the text balloons that use everyday Sundanese. Qualitative and descriptive methods were used in this study by searching for data using observation techniques through interviews and questionnaires, while searching for data from books, papers, the internet and so on. Based on the results of the study, it was found that the influence of the environment and the low understanding of the appropriateness of the Sundanese language in the city of Bandung. The conclusion obtained is by making Sundanese information about the appropriateness of Sundanese language through digital comic media.